Pengaruh Strategi REACT (Relating, Experiencing, Applying, Cooperating, Transfering) Terhadap Hasil Belajar Peserta Didik Pada Materi Asam Dan Basa - Annisa Aulia Harmin; Zulmanelis Darwis; Setia Budi (LPPM Universitas Negeri Jakarta, 2020)
This study aims to determine the effect of the application of REACT Strategies (Relating, Experiencing, Applying, Cooperating, Transfering) to the learning outcomes of students on Acid and Base material. This research was conducted in January-February 2019 at SMA Negeri 39 Jakarta using the Quasy Experimental design, Nonequivalent Control Group Design. The experimental and control groups were each given an initial ability test before learning and post-test after the learning process ended. The experimental group was given a REACT learning strategy while the control group formed a 5M learning strategy. REACT Learning Strategy consists of 5 stages, namely relating, experiencing, applying, cooperating, and transferring. The results showed the average post-test in the experimental group was better than the control group of 77.42 and 66.95. Then the statistical test results obtained tcount> ttable is tcount of 3.64 while ttable with a 5% significance level of 1.67. Related to the application of the REACT learning strategy (Relating, Experiencing, Applying, Cooperating, Transfering) has a positive influence on the learning outcomes of chemistry in Acid and Base materials. Keywords REACT Strategy, Learning Outcomes, Acids and Bases